Blended learning through professional learning communities for water management curriculum among agriculture and technology college teachers - Ratchita Sarimanond; Chantana Viriyavejakul; Paitoon Pimdee (World Journal on Educational Technology Current Issues, 2025)
This study aims to develop and evaluate the effectiveness of a blended learning model facilitated by a professional learning community for teachers of the Water Management Curriculum within agricultural and technology colleges. Although blended learning and professional learning communities have been widely applied in education, their combined use in technical and vocational curricula remains under explored. Data were gathered from key informants, including college directors and experts in educational technology and water management, using semi-structured interviews, small group discussions, and suitability assessment forms. Content analysis was employed alongside descriptive statistics to synthesize findings. The proposed model incorporates four blended learning components, knowledge understanding, collaboration, application, and training, and four professional learning community components, brainstorming, exchanging experiences, supporting, and transferring practical methods. Expert evaluations indicated a high level of suitability for the model, highlighting its potential to enhance instructional quality and foster collaborative professional growth among teachers in specialized technical fields. Keywords: Blended Learning, Professional Learning Community, Community-Based Water Management
Keywords: Online and Blended Learning